Cytokines and the neurodevelopmental basis of mental illness - Ratnayake, Udani; Quinn, Tracey; Walker, David; Dickinson, Hayley (Frontiers in Neuroscience, 2013)
Epidemiological studies suggest that prenatal exposure to different types of viral or bacterial infections may be associated with similar outcomes; i.e., an increased risk of mental illness disorders in the offspring. Infections arising from various causes have similar debilitating effects in later life, suggesting that the exact pathogen may not be the critical factor in determining the neurological and cognitive outcome in the offspring. Instead, it is thought that response of the innate immune system, specifically the increased production of inflammatory cytokines, may be the critical mediator in altering fetal brain development pre-disposing the offspring to mental illness disorders later in life. Inflammatory cytokines are essential for normal brain development. Factors such as the site of cytokine production, a change in balance between anti- and pro- inflammatory cytokines, placental transfer of cytokines, the effects of cytokines on glial cells, and the effects of glucocorticoids are important when evaluating the impact of maternal infection on fetal brain development. Although it is clear that cytokines are altered in the fetal brain following maternal infection, further evidence is required to determine if cytokines are the critical factor that alters the trajectory of brain development, subsequently leading to postnatal behavioural and neurological abnormalities.